Przedsiębiorca — właściciel w społecznej gospodarce rynkowej - Kalina-Prasznic, Urszula (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The foundation of Polish economic system, set out in Article 20 of the constitution, is social market economy based on private property. National accounts are divided into the public and private sector functioning as the opposites, with public and private property accordingly. However, such division raises concerns due to its incompleteness. There are businesses that operate combining the attributes of public and private entities e.g. cooperatives, foundations, societies, employee savings and loan associations, mutual insurance companies. In highly developed economies, they form the third sector based on social property the social sector. Separation and institutionalisation of the third sector and social property in Poland might create conditions more conducive to the achievement of objectives of social market economy than the current dual property structure, unfit to today’s reality and to the nature of social market economy.
Keywords: przedsiębiorca; społeczna gospodarka rynkowa; własność prywatna; własność publiczna; gospodarka dwusektorowa